Role Stressors As A Determinant of Job Performance - Ong Hai Liaw, Jessica; Azan Ridzuan, Ahmad; Azmi Mohd Zainol, Noor; Yaacob, Safar; Mazura Mohaiyadin, Norlaila; Mardzuki, Khairunnisa (International Journal of Engineering and Technology, 2018)
This study examines the correlation between role stressors and job performance using self-administered questionnaires gathered from 327 sample of security personnelâ€™s covers officers and other ranks which involved in administrative and on field operation. The quantitative research has been conducted on security personnelâ€™s who has been deployed in UNIFIL peacekeeping operation mission under United Nation mandate at a Middle Eastern Country. All the dataâ€™s collected has been analyzed by using SmartPLS version 3.0 path model analysis resulted three important findings: first, role overload was not significantly associated with job performance. Second, role conflict was significantly associated with job performance. Third, role ambiguity was not significantly associated with job performance. These results confirm that role stressor (role conflict) is vital and act as important determinant of job performance in the studied organization. Further, this study will be thoroughly offer discussion, implications and conclusion.Â